From the GPS to HM: Place cells, grid cells, and memory. Issue 6 (15th April 2015) - Knierim, James J.
ABSTRACT: A longstanding debate in hippocampus research has revolved around how to reconcile spatial mapping functions of the hippocampus with the global amnesia produced by hippocampal damage in humans. Is the hippocampus primarily a cognitive map used to support spatial learning, or does it support more general types of learning necessary for declarative memory? In recent years, a general consensus has emerged that the hippocampus receives both spatial and nonspatial inputs from the entorhinal cortex. The hippocampus creates representations of experience in a particular spatial and temporal context. This process allows the individual components of experience to be stored in such a way that they can be retrieved together as a conscious recollection. © 2015 Wiley Periodicals, Inc.